শেকড় লতাপাতা ও ঠিকানা - মজুমদার, এ. কে. এম. আবদুল আউয়াল, ১৯৫৭- (ঢাকা : মুক্তচিন্তা, 2015)
Articles chiefly on the life of Samsher Gazi, 1710-1760, ruler from Tripura and parts of Bangladesh.
গ্রন্থপঞ্জিগত নিরদেশিকা অন্তর্ভুক্ত।
BIED
Complimentary copy from BIED
In Bengali.
Keywords: Samsher Gazi, -- 1710-1760.; Tripura (India).; Tripura (India) -- Kings and rulers -- Biography; Bangladesh -- Kings and rulers -- Biography; Tripura (India) -- History -- 18th century; Bangladesh -- History -- 18th century